2014
DOI: 10.1099/mic.0.077685-0
|View full text |Cite|
|
Sign up to set email alerts
|

SecA defects are accompanied by dysregulation of MukB, DNA gyrase, chromosome partitioning and DNA superhelicity in Escherichia coli

Abstract: Spatial regulation of nucleoids and chromosome-partitioning proteins is important for proper chromosome partitioning in Escherichia coli. However, the underlying molecular mechanisms are unknown. In the present work, we showed that mutation or chemical perturbation of secretory A (SecA), an ATPase component of the membrane protein translocation machinery, SecY, a component of the membrane protein translocation channel and acyl carrier protein P (AcpP), which binds to SecA and MukB, a functional homologue of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…We revealed that the ATPase activity of SecA was essential for dynamic localization of these proteins. Integrating the present results with our previous work that SecA/SecY/AcpP genetically interact with MukB and DNA topoisomerases (Adachi et al, 2014 ), we hypothesize that SecA/SecY/AcpP is the core component of the dynamic property of the chromosome segregation proteins in E. coli .…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…We revealed that the ATPase activity of SecA was essential for dynamic localization of these proteins. Integrating the present results with our previous work that SecA/SecY/AcpP genetically interact with MukB and DNA topoisomerases (Adachi et al, 2014 ), we hypothesize that SecA/SecY/AcpP is the core component of the dynamic property of the chromosome segregation proteins in E. coli .…”
Section: Introductionsupporting
confidence: 88%
“…Finally, ADP is converted to ATP and the cycle is repeated again and again (Bauer et al, 2014 ). Previously we have described that SecA, SecY, and A cyl c arrier p rotein P (AcpP) are involved in chromosome partition and that inactivation of SecA causes disorder in decatenation and maintenance of superhelicity on plasmid DNA (Adachi et al, 2014 ). AcpP, which is an acyl carrier protein of ACP complex, acts as a source of acyl groups inside the cell of E. coli .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…52 Other studies reported an attachment at 20-30 membrane sites in addition to oriC. 54,55 Alternately, this linkage might result from an interaction with DNA coupling transcription, translation and insertion of membrane proteins 56,57 i.e. 54,55 Alternately, this linkage might result from an interaction with DNA coupling transcription, translation and insertion of membrane proteins 56,57 i.e.…”
Section: Chromosomal Linkages To the Inner Membranementioning
confidence: 99%
“…Although in addition to the latter also other proteins with more specific functions are involved in the organisation of the nucleoid structure [see e.g. Adachi et al, 2014;Edwards et al, 2013; for a review, see Dame et al, 2011], we primarily consider the effects of the NAPs, which not only regulate the chromosomal dynamics but also act as global regulators of gene expression [Browning et al, 2010;Dillon and Dorman, 2010;Dorman, 2013;Rimsky and Travers, 2011;Travers and Muskhelishvili, 2005a]. Indeed, the comparisons of the genomic NAP binding patterns with spatial transcript profiles revealed remarkable correlations [Scolari et al, 2011].…”
Section: Structural Organisation Of the Bacterial Chromosome: A Briefmentioning
confidence: 99%